A putative 2,3-bisphosphoglycerate-dependent phosphoglycerate mutase is involved in the virulence, carbohydrate metabolism, biofilm formation, twitching halo, and osmotic tolerance in Acidovorax citrulli - Lee, Jongchan; Lee, Jeongwook; Cho, Yongmin; Choi, Junhyeok; Han, Sang-Wook (Frontiers in Plant Science, 2022)
Acidovorax citrulli (Ac) is a gram-negative bacterium that causes bacterial fruit blotch (BFB) disease in cucurbit crops including watermelon. However, despite the great economic losses caused by this disease worldwide, Ac-resistant watermelon cultivars have not been developed. Therefore, characterizing the virulence factors/mechanisms of Ac would enable the development of effective control strategies against BFB disease. The 2,3-bisphosphoglycerate-dependent phosphoglycerate mutase (BdpM) is known to participate in the glycolysis and gluconeogenesis pathways. However, the roles of the protein have not been characterized in Ac. To elucidate the functions of BdpmAc (Bdpm in Ac), comparative proteomic analysis and diverse phenotypic assays were conducted using a bdpmAc knockout mutant (bdpmAc:Tn) and a wild-type strain. The virulence of the mutant to watermelon was remarkably reduced in both germinated seed inoculation and leaf infiltration assays. Moreover, the mutant could not grow with fructose or pyruvate as a sole carbon source. However, the growth of the mutant was restored to levels similar to those of the wild-type strain in the presence of both fructose and pyruvate. Comparative proteomic analyses revealed that diverse proteins involved in motility and wall/membrane/envelop biogenesis were differentially abundant. Furthermore, the mutant exhibited decreased biofilm formation and twitching halo size. Interestingly, the mutant exhibited a higher tolerance against osmotic stress. Overall, our findings suggest that BdpmAc affects the virulence, glycolysis/gluconeogenesis, biofilm formation, twitching halo size, and osmotic tolerance of Ac, suggesting that this protein has pleiotropic properties. Collectively, our findings provide fundamental insights into the functions of a previously uncharacterized phosphoglycerate mutase in Ac.